Moving to Sustainable Buildings: Paths to adopt green innovations in developed countries - Berardi, Umberto (De Gruyter, 2013)
In his Moving to Sustainable Buildings. Paths to Adopt Green Innovations in Developed Countries, Umberto Berardi explores the transition of the construction sector to sustainable building through the adoption of green innovations. Applying methods ranging from theoretical discussions to interviews and field studies, Berardi describes how organisational models among stakeholders are changing as the sector moves towards a green economy. Berardi's book should prove valuable to engineers, architects, environment researchers and policy makers alike, as it successfully weaves together different aspects of green building to create a multidimensional matrix through which sustainable architecture can be understood. Umberto Berardi, an assistant professor at the Worcester Polytechnic Institute (MA, USA), teaches courses on sustainable construction, architectural engineering systems and building physics. He was awarded an MSc from the Politecnico di Bari, an MSc from the University of Southampton (UK) and a PhD from the Scuola Interpolitecnica in Italy. His research areas are related to building acoustics, sustainable constructions and energy saving technologies for buildings. Berardi is also a passionate pianist and a strong proponent of interdisciplinary cooperation between the arts and engineering.